Chlorophyll a fluorescence in transplants of Parmelia sulcata Taylor near a power station (La Robla, Leon, Spain) - Fernandez-Salegui, Ana B.; Calatayud, Ángeles; Terron, Arsenio; Barreno, Eva (2017)
Healthy thalli of Parmelia sulcata Taylor were transplanted to 8 localities in the surroundings of a power station (La Robla, Leon, Spain), the sole pollution source in the region. Changes in chlorophyll a fluorescence were monitored in the transplants 12 months, 18 months and 24 months after transplantation. Statistically significant differences were observed in the ratio of variable to maximal fluorescence, non-photochemical fluorescence quenching and vitality index. The decrease in fluorescence parameters was higher in the localities of Cuadros and Rabanal de Fenar, which are situated a few kilometres away from the power station and in the same direction as the prevailing winds.